Equilibrium Radionuclide Angiocardiography to Select Inotropic Therapy in Patients with Left Ventricular Aneurysm - Maini, C. L.; Bonetti, M. G.; Incalzi, R. Antonelli; Pistelli, R. (Nuklearmedizin - NuclearMedicine, 1986)
Fourteen patients with postinfarctual ventricular aneurysm underwent equilibrium radionuclide angiocardiography at rest (ERNA) before and after oral digoxin administration in order to evaluate the effects of increasing myocardial contractility upon both ventricular aneurysm mechanical behaviour and global ventricular function. The ejection fraction (EF) was not significantly affected by digoxin therapy. However, digoxin induced changes in EF (ΔEF) correlated inversely with changes in aneurysm size and directly with changes in the extent of the hypokinetic area. Two types of aneurysm were observed: a) highcompliance aneurysm the size of which increased after digoxin administration while both EF and the extent of the hypokinetic area fell, and b) low compliance aneurysm for which opposite changes occurred. This different behaviour of ventricular aneurysm may have important practical implications as surgery would be probably more effective than medical treatment in improving resting ventricular function in patients with high-compliance aneurysm.Bei vierzehn Postinfarktpatienten mit ventrikulärem Aneurysma wurde eine Äquilibrium-Radionuklidventrikulographie vor und nach Beginn einer Digoxintherapie durchgeführt, um die Wirkung einer gesteigerten Herzkontraktilität auf das mechanische Verhalten des Aneurysmas und die globale ventrikuläre Funktion zu erfassen. Die Auswurffraktion (EF) veränderte sich nach der Therapie mit Digoxin nicht signifikant. Die Unterschiede der EF (ΔEF) nach Therapie zeigten aber eine umgekehrte Korrelation mit der Größe des Aneurysmas und eine direkte Korrelation mit der Ausdehnung der hypokinetischen Fläche. Zwei Typen von Aneurysma wurden gefunden: a) Aneurysmen mit hoher Compliance, deren Größe nach Therapie mit Digoxin zunimmt, während sich EF und die Ausdehnung der hypokinetischen Fläche verkleinert; b) Aneurysmen mit niedriger Compliance, die sich umgekehrt verhalten. Dieses unterschiedliche Verhalten ventrikulärer Aneurysmen könnte wichtig für die Wahl einer chirurgischen statt einer medizinischen Behandlung zur Verbesserung der ventrikulären Funktion bei Patienten mit Aneurysmen mit hoher Compliance sein.